TEACHING ENGLISH FOR SPECIFIC PURPOSES TO ADULT LEARNERS AT UNIVERSITY: METHODS THAT WORK - Iryna Lytovchenko; Olena Ogienko; Alina Sbruieva; Halyna Sotska (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2018)
As more and more adults in Ukraine and other countries continue to study throughout their lives and may acquire more than one qualification, the average age of students of higher education institutions is increasing, and therefore the foreign language learning at university should be organised in the same way as with working adults. In this regard, it is important to understand that a modern student is an adult learner who has a number of characteristic features that distinguish him/her from a child as a learner and thus should be considered in the learning process. In our article, based on the practical experience of English language teachers of the National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", we aim to show how specific features of adults as learners can be considered in teaching ESP and what learning methods can be most appropriate for that purpose. We conducted a mini-research among 12 English teachers of Department of English for Engineering, who had the opportunity to work with both children and adult learners. As a data collection tool, we used an open-ended questionnaire which included three questions concerning their perception of university students as adult learners, importance of creating favourable learning climate, methods, and technologies they find most effective and motivating for adult students. As shown by the results of our survey, teachers find interactive ESP learning methods and techniques the most effective, since they most fully involve adult students in self-directed learning, permit taking into account characteristic features of adults as learners, make learning a collaborative process involving cooperation between all the participants as the main driving force of the learning process.